Evaluación del clima organizacional y su relación con la satisfacción laboral del personal administrativo del Municipio de Loja en el año 2024 - Rojas Paladines, Cynthia Estefany (2024)
This study was conducted in the Municipality of Loja with the aim of evaluating the organizational climate and its relationship with job satisfaction among administrative staff. Recognizing that human capital is essential for the development of organizations, the research examined how the work environment influences performance and the achievement of institutional objectives. The investigation focused on two main variables: organizational climate, measured through a questionnaire based on eight Likert dimensions: working conditions, interpersonal relationships, internal communication, organizational structure, professional training, recognition and promotion, motivation and satisfaction, and psychosocial aspects. Job satisfaction was analyzed through Herzberg's Two-Factor Theory, assessing both intrinsic (motivational) and extrinsic (working condition) factors. A statistical analysis of these dimensions was conducted to determine their correlation with job satisfaction. The results revealed a significant correlation between a favorable organizational climate and higher job satisfaction among administrative personnel. Based on these findings, strategies were proposed to enhance job satisfaction within the organization.